The Relationship Between Proprioception and Badminton Player Shot Landing Accuracy - Yichen Bao, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2024)
This research aims to examine the relationship between the proprioception of college-level badminton athletes and their accuracy in badminton tosses. The study utilizes five proprioception testing methods, including joint position sense, movement sense, force sense, and strength to assess the proprioception integrity of the athletes. The testing indicators include upper limb muscle proprioception, upper arm muscle proprioception, lower limb proprioception, kinesthetic proprioception, and upper limb kinesthetic accuracy. The results indicate significant differences (P < 0.05) in the force sensation of upper limb muscles among players with varying levels of skill in the high serve. Furthermore, a correlation exists between the force sensation of upper limb muscles and the accuracy of the forehand clear (P > 0.05). Significant differences (P < 0.05) were also observed in the force sensation of upper limb muscles among players at different skill levels in the forehand clear. The force sensation of upper limb muscles is correlated with hitting accuracy, suggesting its importance for the accuracy of shuttlecock landing locations during the stable phase of motion patterns. This paper provides substantial evidence that proprioception training can enhance the performance of badminton athletes and offers theoretical support for innovative selection methods in badminton sports.